Pressurized hot water extraction of anthraquinones from Heterophyllaea pustulata Hook f. (Rubiaceae) - Barrera Vazquez, Maria Fernanda (2015)
Heterophyllaea Pustulata Hook. f. (Rubiaceae), commonly known as "cegadera", is a phototoxic native plant from South America, containing anthraquinones with important antibacterial, antiviral and anticancer activity. In this work, pressurized hot water extraction (PHWE) was applied to extract anthraquinones from the stems of the plant. The effect of temperature, pressure and water flow rate on the extraction yield of four anthraquinones (soranjidiol, rubiadin, rubiadin 1-methyl ether and 2-hydroxy-3-methyl anthraquinone) was studied. Within the experimental range explored, the optimum extraction temperature was 170 ºC. Lower yields were obtained at higher temperatures, apparently due to the thermal decomposition of these anthraquinones. The experimental extraction curves were fitted with three models: the thermodynamic partitioning and the one-site and two-site kinetic models.